Gene therapy for established murine collagen-induced arthritis by local and systemic adenovirus-mediated delivery of interleukin-4 - Kim, Seon Hee (BioMed Central, 2000)
INTRODUCTION: Rheumatoid arthritis (RA) is a chronic systemic autoimmune disease that is characterized by joint inflammation, and progressive cartilage and bone erosion. Recent research has identified certain biologic agents that appear more able than conventional therapies to halt effectively the progression of disease, as well as ameliorate disease symptoms. One potential problem with the use of biologic agents for arthritis therapy is the need for daily or weekly repeat dosing. The transfer of genes directly to the synovial lining can theoretically circumvent the need for repeat dosing and reduce potential systemic side effects [1,2]. However, although many genes have been effective in treating murine CIA if administrated at a time before disease onset, local intra-articular or periarticular gene transfer has not been highly effective in halting the progression of established disease. IL-4, similar to tumor necrosis factor (TNF)-α and IL-1 inhibitors, has been shown be therapeutic for the treatment of murine CIA when administered intravenously as a recombinant protein, either alone or in combination with IL-10. IL-4 can downregulate the production of proinflammatory and T-helper (Th)1-type cytokines by inducing mRNA degradation and upregulating the expression of inhibitors of proinflammatory cytokines such as IL-1 receptor antagonist (IL-1Ra) [3,4]. IL-4 is able to inhibit IL-2 and IFN-γ production by Th1 cells, resulting in suppression of macrophage activation and the production of the proinflammatory cytokines IL-1, IL-6, IL-8, and TNF-α by monocytes and macrophages [4,5,6,7,8,9]. OBJECTIVE: In order to examine the therapeutic effects of local and systemic IL-4 expression in established CIA, an adenoviral vector carrying the gene for murine IL-4 (Ad-mIL-4) was generated. The ability of Ad-mIL-4 to treat established CIA was evaluated by local periarticular and systemic intravenous injection of Ad-mIL-4 into mice at various times after disease onset. MATERIALS AND METHODS: Male DBA/1 lacJ (H-2(q)) mice, aged 7-8 weeks, were purchased from The Jackson Laboratory (Bar Harbor, ME, USA). The mice were immunized intradermally at the base of tail with 100 μ g bovine type II collagen. On day 21 after priming, mice received a boost injection (intradermally) with 100 μ g type II collagen in incomplete adjuvant. For the synchronous onset of arthritis, 40 μ g lipopolysaccharide (Sigma, St Louis, MO, USA) was injected intraperitoneally on day 28. Ad-mIL-4 was injected periarticularly into the hind ankle joints of mice on day 32 or intravenously by tail vein injection on day 29. Disease severity was monitored every other day using an established macroscopic scoring system ranging from 0 to 4: 0, normal; 1, detectable arthritis with erythma; 2, significant swelling and redness; 3, severe swelling and redness from joint to digit; and 4, maximal swelling with ankylosis. The average of macroscopic score was expressed as a cumulative value for all paws, with a maximum possible score of 16 per mouse. Cytokine production by joint tissue or serum were assessed using enzyme-linked immunosorbent assay (ELISA; R&D Systems, Minneapolis, MN, USA). RESULTS: To examine the therapeutic effects of IL-4 gene transfer in a murine model of arthritis, 5×10(8) particles of Ad-mIL-4 and enhanced green fluorescent protein (Ad-eGFP) were administered by periarticular injection into the ankle joints of mice with established disease 4 days after lipopolysaccharide injection. All mice had established disease at time of injection. As shown in Figure 1, the severity of arthritis (Fig. 1a), paw thickness (Fig. 1b), and the number of arthritic paws (Fig. 1c) were all significantly reduced in the Ad-mIL-4 group, compared with the saline- and Ad-eGFP-treated groups. Analysis of the bones in the ankle joints of control arthritic mice showed evidence of erosion with an associated monocytic infiltrate around the joint space compared with the Ad-mIL-4-treated and nonarthritic control joints. In addition, injection of the ankle joints in the hind legs resulted in a therapeutic effect in the front paws. A similar contralateral effect has been observed with adenoviral-mediated delivery of viral (v)-IL-10. Interestingly, a high level of murine IL-10 also was detected from the joint lysates of Ad-mIL-4-treated naïve and arthritic mice, with the production of endogenous IL-10 correlating with the dose of Ad-mIL-4. The administration of recombinant IL-4 protein systemically has been shown to be therapeutic in murine CIA models if given before disease onset. To examine the effect of systemic IL-4 delivered by gene transfer, 1×10(9) particles of Ad-mIL-4 were injected via the tail vein of collagen-immunized mice the day after lipopolysaccharide injection. Whereas the immunized control mice, injected with Ad-eGFP, showed disease onset on day 3 after lipopolysaccharide injection, Ad-mIL-4-treated mice showed a delay in disease onset and as a reduction in the total number of arthritic paws. Also, systemic injection of Ad-mIL-4 suppressed the severity of arthritis in CIA mice according to arthritis index. DISCUSSION: Gene therapy represents a novel approach for delivery of therapeutic agents to joints in order to treat the pathologies associated with RA and osteoarthritis, as well as other disorders of the joints. In the present study we examined the ability of local periarticular and systemic gene transfer of IL-4 to treat established and early-stage murine CIA, respectively. We have demonstrated that both local and systemic administration of Ad-mIL-4 resulted in a reduction in the severity of arthritis, as well as in the number of arthritic paws. In addition, the local gene transfer of IL-4 reduced histologic signs of inflammation and of bone erosion. Interestingly, local delivery of Ad-mIL-4 was able to confer a therapeutic effect to the untreated, front paws through a currently unknown mechanism. In addition, both local and systemic expression of IL-4 resulted in an increase in the level of endogenous IL-10, as well as of IL-1Ra (data not shown). Previous experiments have shown that gene transfer of IL-10 and IL-1 and TNF inhibitors at the time of disease initiation (day 28) is therapeutic. However, delivery of these agents after disease onset appeared to have only limited therapeutic effect. In contrast, the present results demonstrate that IL-4, resulting from local periarticular and systemic injection of Ad-mIL-4, was able partially to reverse progression of established and early-stage disease, respectively. These results, as well as those of others, support the potential application of IL-4 gene therapy for the clinical treatment of RA.